Structural phases and Maxwell–Wagner relaxation in magnetically soft-ZnFe2O4 and hard-Sr2Cu2Fe12O22 nanocomposites. Issue 2 (1st February 2016) - Jotania, Rajshree B.; Nandotaria, Reshma A.; Chauhan, Chetna C.; Hashim, Mohd.; Singh Meena, Sher; Shirsath, Sagar E.
Abstract: In the present investigation magnetically soft-ZnFe2 O4 (S-spinel) and hard-Sr2 Cu2 Fe12 O22 (Y type) mixed ferrite nano-composites (S:Y as 1:0, 1:0, 1:1, 1:2, 1:4, 1:8 and 0:1) were synthesized by using chemical co-precipitation technique. X-ray diffraction analysis revealed the formation of mixed ferrite phases containing Y-type hexaferrite and spinel ferrite phases. The particle size of the prepared samples was estimated from transmission electron microscopy and it lies within the nanometer range. Fourier transform infrared spectroscopy was employed to determine the local symmetry in the crystalline solids and to shed light on the ordering phenomenon of ferrite nano-composite. Curie temperature of all the samples was evaluated using AC susceptibility measurements. Dielectric constant and loss factor was studied as a function of frequency and it is found to be minimum for pure soft ferrite and increased with increase in the concentration of hard ferrite. The results were interpreted in terms of the two-layer model that conducting grains partitioned from each other by poorly conducting grain boundaries. This dielectric dispersion was well explained in terms of Maxwell–Wagner relaxation.